LUXURY BRAND SHIFTING TARGET INTO THE MILLENNIAL, DOES IT FIT WITH THE INDONESIAN JUNIOR MILLENNIAL MARKET? - Sarah, Cut
At present, millennial generation represents 32% of luxury goods consumers. Forbes predicts this figure will increase to 50% of the total market in 2025. Junior millennial have unique behavioral and value characteristics, this requires companies to understand them better. Luxury goods companies have changed their target market to millennial generation, using a global strategy of multinational companies trying to approach millennial generation in Indonesia. Louis Vuitton, as the most valuable luxury brand in the world, through Louis Vuitton Monnet Hennesy (LVMH) opened its first store in Jakarta in 2009. In 2015, the company began to change its target market to millennial generation. The strategies used are like offering collections to the younger generation and recruiting sales advisers from junior millennial. As a global luxury brand, all policies are centralized, where all decisions are decided by the central LVMH in Paris, France. Louis Vuitton Indonesia faces several problems such as differences in behavior of Indonesian millennial generation compared to global millennial generation. This study will discuss the big picture of the luxury brand fashion industry and Louis Vuitton Indonesia's current marketing strategy. The big picture of the external environment was identified through PESTEL analysis and competition analysis. For Louis Vuitton Indonesia's internal environment analyzed through 8P's Luxury Marketing Mix. In identifying marketing strategies used by companies, this study conducted interviews with store and client operational teams. In the final section, the study proposes marketing strategies for junior millennial. The choice of differentiation strategy is the strategy set in millennial marketing. To respond to the problems faced by Louis Vuitton Indonesia, companies must develop marketing strategies to increase the desire of Indonesian millennial generation towards their brands. By offering a more diverse collection, instalment and price-cutting programs, and celebrity endorsement, it is hoped that it can increase the desires of Indonesia's millennial generation and corporate income.